1994
DOI: 10.1007/bf00588069
|View full text |Cite
|
Sign up to set email alerts
|

MRI of the brain in diabetes mellitus

Abstract: We studied the MRI appearances of the brain in 159 patients with diabetes mellitus (DM) and 2566 age-matched individuals without DM (controls). The images were reviewed for cerebral infarcts, hemorrhage, atrophy and subcortical arteriosclerotic encephalopathy. Cerebral atrophy was significantly more frequent in patients with DM than in controls (P > 0.005) from the sixth to the eighth decade. The frequency of atrophy was 41.2% in the 6th decade, 60.0% in the 7th and 92.3% in the 8th decade in DM, and 19.8%, 38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
73
1
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(80 citation statements)
references
References 7 publications
5
73
1
1
Order By: Relevance
“…Central and peripheral atrophy in type 1 diabetes [7,8,18] and subcortical white matter lesions [4,5] have been reported in the literature. The methods used in these studies are semiquantitative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Central and peripheral atrophy in type 1 diabetes [7,8,18] and subcortical white matter lesions [4,5] have been reported in the literature. The methods used in these studies are semiquantitative.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the few neuroradiological studies that have assessed structural brain abnormalities in patients with type 1 diabetes have demonstrated conflicting results [4][5][6][7][8]. The majority of these studies have been based on manual or semi-automated region-of-interest-guided measurements, which may be inherently biased.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies employing in vivo brain imaging have reported 'accelerated brain ageing' in patients with diabetes (for example [4,6]). In addition, among individuals with type 2 diabetes, reductions in cognitive functioning have been reported to be associated with white matter lesions, atrophy and the presence of infarcts [4].…”
Section: Introductionmentioning
confidence: 99%
“…Although it is known that diabetic patients are at increased risk for stroke (2), little is known about the risk for other brain pathology, such as that associated with neurodegeneration or small vessel disease. Previous radiological studies of patients with diabetes were based on highly selective groups of individuals referred to computed tomography or magnetic resonance imaging (MRI) neuroimaging (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Only a few population-based studies assessed the association of diabetes-as one of many cardiovascular disease (CVD) risk factors-to only one specific type of brain lesion (18 -22).…”
mentioning
confidence: 99%